Vortioxetine Improves Depressive Symptoms and Cognition in Parkinson’s Disease Patients with Major Depression: An Open-Label Prospective Study - Diego Santos García; Maria Gema Alonso Losada; Icíar Cimas Hernando; Iria Cabo López; Rosa Yáñez Baña; Ruben Alonso Redondo; Jose Manuel Paz González; Carlos Cores Bartolomé; Maria José Feal Painceiras; Maria Cristina Íñiguez Alvarado; Carmen Labandeira; Iago García Díaz (Brain Sciences, 2022)
Depression is frequent in Parkinson’s disease (PD) patients, but the evidence for many antidepressant agents to treat it in PD is insufficient. The aim of the present prospective open-label single-arm study (VOPARK, an open-label study of the effectiveness and safety of VOrtioxetine in PARKinson’s disease patients with depression) was to analyze the effectiveness of vortioxetine on depressive symptoms in PD patients with major depression. The primary efficacy outcome was the change from baseline (VB) at the end of the observational period (12 weeks ± 14 days; V12w) in the 17-item Hamilton Depression Rating Scale (HAM-D17) total score. At VB, all patients had a HAM-D17 total score ≥16. A total of 30 patients (age 66.23 ± 10.27; 73.3% males) were included between February 2021 (first patient, 12/FEB/21) and March 2022 (last patient, 14/MAR/22). At 12 weeks, 27 patients completed the follow-up (90%). The total HAM-D17 total score was reduced by 52.7% (from 21.5 ± 4.75 at VB to 10.44 ± 7.54 at V12w; Cohen’s effect size = −2.5; p < 0.0001) and the response and remission rates were 50% and 43.3%, respectively. Apathy (Apathy Scale; p < 0.0001), cognition (PD-Cognitive Rating Scale; p = 0.007), fatigue (Fatigue Severity Scale; p = 0.014), and quality of life (PDQ-39 (p = 0.001) and EUROHIS-QOL8 (p < 0.0001)) improved at 3 weeks as well. A total of 11 adverse events in 10 patients (33.3%) were reported, one of which was severe (vomiting related to vortioxetine with full recovery after drug withdrawal). Vortioxetine was safe and well tolerated and improved depressive symptoms and other non-motor symptoms in PD patients.